2023
DOI: 10.3390/metabo13020236
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic Strategies to Improve Chemical Information from OSMAC Studies of Endophytic Fungi

Abstract: Metabolomics strategies are important tools to get holistic chemical information from a system, but they are scarcely applied to endophytic fungi to understand their chemical profiles of biosynthesized metabolites. Here Penicillium sp. was cultured using One Strain Many Compounds (OSMAC) conditions as a model system to demonstrate how this strategy can help in understanding metabolic profiles and determining bioactive metabolites with the application of metabolomics and statistical analyses, as well as molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…A recent publication combined the OSMAC approach with metabolomic, statistical, and networking analyses to reveal antibacterial properties of endophytic Penicillium sp. and found the polyketides austalides and viridicatumtoxin A, a rare tetracycline (da Silva et al., 2023).…”
Section: Sm Mining and “Biosynthetic Dark Matter”mentioning
confidence: 99%
“…A recent publication combined the OSMAC approach with metabolomic, statistical, and networking analyses to reveal antibacterial properties of endophytic Penicillium sp. and found the polyketides austalides and viridicatumtoxin A, a rare tetracycline (da Silva et al., 2023).…”
Section: Sm Mining and “Biosynthetic Dark Matter”mentioning
confidence: 99%
“…One such strategy is the one strain many compounds (OSMAC) approach, which is based on the theory that a single strain is able to produce many compounds in different growth conditions to access the cryptic metabolic pathways that are otherwise silent (Pinedo-Rivilla et al 2022). Culture conditions can significantly impact the production of natural products, resulting in either upregulation or downregulation of certain compounds or even the production of new metabolites through the activation of cryptic biosynthetic pathways (Da Silva et al 2023). Many studies have reported the impact of cyanobacterial culture conditions with various objectives: to increase biomass or lipid content, to improve the production of bioactive compounds, or to investigate the ecology and physiology of strains related to harmful algal blooms (Crnkovic et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Culture conditions can significantly impact the production of natural products, resulting in either upregulation or downregulation of certain compounds or even the production of new metabolites through the activation of cryptic biosynthetic pathways (Da Silva et al . 2023). Many studies have reported the impact of cyanobacterial culture conditions with various objectives: to increase biomass or lipid content, to improve the production of bioactive compounds, or to investigate the ecology and physiology of strains related to harmful algal blooms (Crnkovic et al .…”
Section: Introductionmentioning
confidence: 99%